Rates of retention of persons with a mental health disorder in outpatient smoking cessation and reduction trials, and associated factors: protocol for a systematic review and meta-analysis - Luke Wolfenden; Gemma Taylor; John Wiggers; Alexandra Patricia Metse; Emily Stockings; Jacqueline Bailey; Timothy Regan; Kate Bartlem; Jenny Bowman (BMJ Open)
Introduction Smoking among persons with a mental health disorder is associated with inequitable health, social and economic burden. Randomised controlled trials (RCTs) are considered the gold standard design for the assessment of healthcare intervention efficacy/effectiveness. However, many RCTs of smoking interventions for persons with a mental health disorder lack rigour due to low participant retention. No systematic review has pooled retention rates in randomised trials of smoking interventions for persons with a mental health disorder or explored associated factors. The aims of the systematic review will therefore be to: (1) summarise overall rates of participant retention in smoking cessation and reduction trials involving persons with a mental health disorder (including for experimental and control groups separately) and (2) determine if retention rates vary according to participant, environmental, researcher and study factors.Methods and analysis PsycINFO, EMBASE, MEDLINE, CENTRAL and The Cochrane Tobacco Addiction Review Group Specialised Register will be searched for reports of RCTs of outpatient smoking cessation or reduction interventions for adults with a mental health disorder. The search terms will include MeSH terms and free text words, and there will be no language or date restrictions. All databases will be searched from inception to present. Data will be analysed using the Mantel-Haenszel fixed-effect model, and where substantial heterogeneity (I2 >50%) is detected, DerSimonian & Laird inverse-variance random effects model. Pooled estimates and 95% CIs will be calculated for overall participant retention rates and for intervention and control trial arms separately. Associations between participant retention and participant, environmental, researcher and study factors will be assessed via subgroup analyses and, where sufficient data are obtained, meta-regression.Ethics and dissemination This study does not require ethical approval. The findings of this review will be disseminated via publication in a peer-reviewed open access medical journal and presentations at international scientific meetings.